1996
DOI: 10.1159/000172427
|View full text |Cite
|
Sign up to set email alerts
|

Enteric Physiology of the Transplanted Gut: Absorption and Motility

Abstract: Tremendous progress has been made recently in small bowel transplantation. However, our understanding of the enteric function of the transplanted gut remains in its infancy. Unlike many of the other organs commonly transplanted, the function of the transplanted gut appears to be markedly affected by the consequences of the transplantation procedure (denervation, lymphatic disruption, and immune phenomena). This review discusses the effects of gut transplantation on segmental enteric function, concentrating on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 56 publications
(74 reference statements)
1
9
0
Order By: Relevance
“…1 Unlike the heart, lung, kidney, and liver, which function quite well despite the complete organ isolation and the obligate denervation necessitated by the transplantation procedure, small intestinal function is modulated extensively by extrinsic and enteric neural input. [2][3][4][5] The study of these aspects of gut dysfunction after transplantation in animal models will help us to understand the underlying mechanisms mediating the enteric dysfunction of transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…1 Unlike the heart, lung, kidney, and liver, which function quite well despite the complete organ isolation and the obligate denervation necessitated by the transplantation procedure, small intestinal function is modulated extensively by extrinsic and enteric neural input. [2][3][4][5] The study of these aspects of gut dysfunction after transplantation in animal models will help us to understand the underlying mechanisms mediating the enteric dysfunction of transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the secretion and absorption function of intestinal graft is one of the most important factors for successful intestinal transplantation. The studies have demonstrated that intestinal absorptive function has been impaired following small intestinal transplantation [5], [6], and the defects in intestinal absorptive function occur even in nonrejecting small intestinal grafts [7], [8]. However, intestinal secretion function after intestinal transplantation is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…The surgical technique leads to extrinsic denervation, disruption of intrinsic neural continuity, and lymphatic transection. There is evidence that after small-bowel transplantation (SBTx) fasting motility is controlled by the intrinsic nervous system, but is temporally dissociated with that of the native intestinal remnant [28]. Extrinsic sympathetic re-innervation can occur partially during the first year after transplantation, but its efficacy on motility control is expected to be poor [20].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the lymphatic vessels can regenerate within a few weeks after transplantation without major improvement in absorption. Moreover, it has been demonstrated that circulating hormones do not alter temporal coordination of intestinal motor patterns [28].…”
Section: Introductionmentioning
confidence: 99%